Toner
By combining crystalline resin and non-crystalline resin in toner and adjusting their interaction, the problem of sharp increase in viscosity when existing toner cures at low temperatures is solved, and the color reproducibility and gloss uniformity are improved, while taking into account high heat preservation performance.
Patent Information
- Application Number
- JP2023175090
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-22
AI Technical Summary
When existing crystalline resins cure at low temperatures, their viscosity increases sharply, resulting in poor color reproducibility and gloss uniformity, and it is difficult to take into account both the heat preservation and low temperature curing properties.
Using toner containing a combination of crystalline resin and amorphous resin, by adjusting the interaction between the crystalline resin and the release agent, the viscosity change of the toner during the curing process is controlled, thereby improving color reproducibility and gloss uniformity.
Toner with excellent curing performance and high heat preservation performance at low temperatures is achieved, ensuring color reproducibility and gloss uniformity.
Smart Images

Figure 2025065704000009 
Figure 2025065704000001 
Figure 2025065704000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to toners used in electrophotography and electrostatic recording. [Background technology]
[0002] Energy conservation is also considered a major technical issue in electrophotographic devices, and significant reductions in the energy required for fixing devices are being considered. For toner, technologies to improve so-called "low-temperature fixing property" that enables fixing with lower energy are being considered.
[0003] As a method for enabling fixing at low temperatures, a technology using a crystalline resin as the binder resin of the toner is being considered. Crystalline resins have excellent heat resistance and storage stability because the molecular chains are regularly arranged and they hardly soften at temperatures lower than their melting point. On the other hand, when the melting point is exceeded, the crystals melt suddenly, which is accompanied by a rapid drop in viscosity. For this reason, crystalline resins are attracting attention as materials that have excellent sharp melting properties and low-temperature fixing properties.
[0004] Usually, crystalline vinyl resins have long-chain alkyl groups as side chains, and the long-chain alkyl groups in the side chains are oriented to each other to exhibit crystallinity. Patent Document 1 discloses a toner using a crystalline vinyl resin, which is a copolymer of a polymerizable monomer having a long-chain alkyl group and a non-crystalline polymerizable monomer having a different SP value from the polymerizable monomer, as a toner using a crystalline vinyl resin. Furthermore, Patent Document 2 discloses a toner in which a polymerizable crosslinking agent is added or increased in amount, and a gel component exhibiting high elasticity is increased in order to suppress deterioration in hot offset resistance and heat-resistant storage stability that accompanies the addition of a crystalline resin to improve low-temperature fixing ability. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2020-173414 A [Patent Document 2] JP 2018-151619 A Summary of the Invention [Problem to be solved by the invention]
[0006] As mentioned above, when crystalline resins exceed their melting point, they undergo a rapid drop in viscosity as they melt. This is an excellent characteristic from the viewpoint of low-temperature fixability. On the other hand, crystalline resins also have a fast crystallization rate, so when they are cooled from a molten state, their viscosity rises rapidly. Issues with a fast crystallization rate include poor color reproducibility, which occurs because the viscosity rise begins before the colors are fully mixed. Another issue is the lack of gloss uniformity of the fixed image, which occurs because the volumetric shrinkage rate differs depending on the amount of toner applied. The present disclosure is directed to a toner that has excellent low-temperature fixing properties and heat-resistant storage stability, and further exhibits good color reproducibility and gloss uniformity of fixed images. [Means for solving the problem]
[0007] The present disclosure relates to a toner having toner particles containing a binder resin and a release agent, The binder resin includes a crystalline resin and an amorphous resin, In a differential scanning calorimetric measurement of the toner, the toner was heated from 20° C. to 180° C. at a heating rate of 10° C. / min to obtain a differential scanning calorimetric curve A, then held at 180° C. for 10 minutes, and then cooled from 180° C. to 10° C. at a heating rate of 10° C. / min to obtain a differential scanning calorimetric curve B. The differential scanning calorimetric curve A has an endothermic peak m(B) derived from the crystalline resin and an endothermic peak m(W) derived from the release agent, The differential scanning calorimetric curve B has an exothermic peak c(B) derived from the crystalline resin and an exothermic peak c(W) derived from the release agent, The peak temperature (°C) of the endothermic peak m(B) is designated as Tm(B), and the peak temperature (°C) of the endothermic peak m(W) is designated as Tm(W), When the peak temperature (°C) of the exothermic peak c(B) is Tc(B) and the peak temperature (°C) of the exothermic peak c(W) is Tc(W), The Tm(B), the Tc(B), the Tm(W) and the Tc(W) are 50.0≦Tm(B)≦80.0 15.0≦Tm(B)-Tc(B)≦25.0 Tc(W)≦Tm(B) 15.0≦Tm(W)-Tc(W)≦25.0 Fulfilling The storage modulus G'(TmB) of the toner at Tm(B) [°C] is 1.0×10 5 ~1.0×10 8 Pa, relating to the toner. Effect of the Invention
[0008] The present disclosure can provide a toner that has excellent low-temperature fixing property and heat-resistant storage stability, and further exhibits good color reproducibility and gloss uniformity of fixed images. [Brief description of the drawings]
[0009] [Figure 1] Example of sample attachment for viscoelasticity measurement DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In the present disclosure, the description of a numerical range such as "XX or more and YY or less" or "XX to YY" means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. The (meth)acrylic acid ester means an acrylic acid ester and / or a methacrylic acid ester.
[0011] In addition, in the present disclosure, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ. The term "monomer unit" refers to the reacted form of a monomer substance in a polymer. For example, one section of carbon-carbon bond in the main chain of a polymer in which a vinyl monomer is polymerized is considered to be one unit. A vinyl monomer can be represented by the following formula (6). [ka]
[0012] In formula (6), R A represents a hydrogen atom or an alkyl group (preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group); R B represents an optional substituent. In the present disclosure, a crystalline resin refers to a resin that shows a clear endothermic peak in a differential scanning calorimeter (DSC) measurement.
[0013] The present inventors have conducted research to solve the above-mentioned problems. From the viewpoint of low-temperature fixability, a technology for accelerating the rate of decrease in melt viscosity is required for toner before fixing. On the other hand, from the viewpoint of color mixing and gloss uniformity, a technology for slowing down the increase in melt viscosity to some extent is required for toner during fixing. Generally, crystalline resins have the property of fast melting and crystallization rates, and this property has been utilized in technology for improving low-temperature fixability. Therefore, the fast rate of increase in viscosity of toner during fixing is the property of crystalline resins, and no attempt has been made to deliberately slow down the increase in melt viscosity.
[0014] In order to solve the above problem, the inventors have repeatedly studied whether it is possible to appropriately control only the viscosity increase rate of the toner during fixing without changing the viscosity decrease rate of the toner before fixing. In the fixing process, it is possible to soften and mix multiple resin components in the toner by applying heat and pressure, so the inventors thought that the above problem could be solved by using this to control the crystallization rate of the toner during fixing. The form for achieving this is described below. The present inventors have found that the following toner has excellent low-temperature fixing property and heat-resistant storage stability, and further has excellent color reproducibility and image gloss uniformity.
[0015] The present disclosure relates to a toner having toner particles containing a binder resin and a release agent, The binder resin includes a crystalline resin and an amorphous resin, In a differential scanning calorimetric measurement of the toner, the toner was heated from 20° C. to 180° C. at a heating rate of 10° C. / min to obtain a differential scanning calorimetric curve A, then held at 180° C. for 10 minutes, and then cooled from 180° C. to 10° C. at a heating rate of 10° C. / min to obtain a differential scanning calorimetric curve B. The differential scanning calorimetric curve A has an endothermic peak m(B) derived from the crystalline resin and an endothermic peak m(W) derived from the release agent, The differential scanning calorimetric curve B has an exothermic peak c(B) derived from the crystalline resin and an exothermic peak c(W) derived from the release agent, The peak temperature (°C) of the endothermic peak m(B) is designated as Tm(B), and the peak temperature (°C) of the endothermic peak m(W) is designated as Tm(W), When the peak temperature (°C) of the exothermic peak c(B) is Tc(B) and the peak temperature (°C) of the exothermic peak c(W) is Tc(W), The Tm(B), the Tc(B), the Tm(W) and the Tc(W) are 50.0≦Tm(B)≦80.0 15.0≦Tm(B)-Tc(B)≦25.0 Tc(W)≦Tm(B) 15.0≦Tm(W)-Tc(W)≦25.0 Fulfilling The storage modulus G'(TmB) of the toner at Tm(B) [°C] is 1.0×10 5 ~1.0×10 8 Pa, relating to the toner.
[0016] The toner of the present disclosure will be described. The toner has toner particles containing a binder resin and a release agent. The binder resin contains a crystalline resin and an amorphous resin. By containing a crystalline resin in the binder resin, it is possible to ensure the heat-resistant storage stability of the toner while exhibiting low-temperature fixability. As described above, the toner is required to have a high storage modulus up to a temperature required for heat-resistant storage stability, and to have a sharp drop in storage modulus at a temperature higher than that, that is, to exhibit sharp melt properties. As described above, a crystalline resin can be given as a material exhibiting sharp melt properties.
[0017] Further, in the differential scanning calorimetry of the toner, the temperature is raised from 20° C. to 180° C. at a temperature rise rate of 10° C. / min to obtain a differential scanning calorimetry curve A. Then, the toner is held at 180° C. for 10 minutes, Next, the temperature is decreased from 180°C to 10°C at a rate of 10°C / min to obtain a differential scanning calorimetric curve B. At this time, the differential scanning calorimetric curve A has an endothermic peak m(B) derived from the crystalline resin and an endothermic peak m(W) derived from the release agent. In addition, the differential scanning calorimetric curve B has an exothermic peak c(B) derived from the crystalline resin and an exothermic peak c(W) derived from the release agent.
[0018] Then, when the peak temperature (°C) of endothermic peak m(B) is Tm(B), the peak temperature (°C) of endothermic peak m(W) is Tm(W), the peak temperature (°C) of exothermic peak c(B) is Tc(B), and the peak temperature (°C) of exothermic peak c(W) is Tc(W), Tm(B), Tc(B), Tm(W), and Tc(W) satisfy the following formula: 50.0≦Tm(B)≦80.0 15.0≦Tm(B)-Tc(B)≦25.0 Tc(W)≦Tm(B) 15.0≦Tm(W)-Tc(W)≦25.0
[0019] Tm(B) represents the melting point of the crystalline resin. When Tm(B) is 50.0°C or more, good heat-resistant storage stability can be obtained. It is preferably 55.0°C or more, more preferably 58.0°C or more. When Tm(B) is 80.0°C or less, good low-temperature fixability can be obtained. Tm(B) is preferably 75.0°C or less, more preferably 70.0°C or less. Tm(B) is preferably 55.0 to 75.0°C, more preferably 58.0 to 70.0°C. Tm(B) can be controlled by the type and molecular weight of the crystalline resin. For example, the weight average molecular weight of the crystalline resin is preferably 20,000 to 40,000, and more preferably 25,000 to 40,000.
[0020] Tm(B)-Tc(B) represents the difference between the temperature at which a crystalline resin is melted by heat and the temperature at which it is cooled again after melting and crystallized, in other words, the crystallization speed. A small Tm(B)-Tc(B) represents a fast crystallization speed, and a large Tm(B)-Tc(B) represents a slow crystallization speed. This value is considered to measure the thermal properties equivalent to the speed at which the toner melts due to heat in the fixing member and the melt viscosity decreases, and then cools after passing through the fixing section and the melt viscosity increases during the electrophotographic fixing process.
[0021] Since one of the characteristics of crystalline resins is their fast crystallization rate, it has been considered difficult to control only the crystallization rate by speeding up the melting rate alone. The toner of the present disclosure has Tm(B)-Tc(B) of 15.0°C or higher. Tm(B)-Tc(B) is preferably 17.0°C or higher. This range indicates that the crystallization rate is slower than that of conventional crystalline resins.
[0022] The present inventors have found that good color reproducibility can be obtained by setting Tm(B)-Tc(B) in the above range. This is believed to be because, with a crystallization speed in the above range, the colors in a multi-color image are thoroughly mixed during fixing before the melt viscosity increases. The present inventors have also found that the gloss uniformity of the fixed image can be improved by setting Tm(B)-Tc(B) in the above range. This is believed to be because, with a crystallization speed in the above range, the difference in volumetric shrinkage rate between areas with a large amount of toner and areas with a small amount of toner can be reduced.
[0023] Furthermore, the toner of the present disclosure has a Tm(B)-Tc(B) of 25.0° C. or less. Tm(B)-Tc(B) is preferably 22.0° C. or less. The present inventors have found that when Tm(B)-Tc(B) is in the above range, the gloss uniformity of the fixed image is good. This is believed to be because the crystallization speed is not too slow and is appropriate, which makes it possible to suppress the fixed image from being affected by the unevenness of the paper and resulting in non-uniform gloss. Tm(B)-Tc(B) is preferably The temperature is preferably 17.0 to 22.0°C, and more preferably 19.0 to 22.0°C. Moreover, Tc(B) is preferably 30.0 to 60.0°C, and more preferably 40.0 to 50.0°C.
[0024] In order to control Tm(B)-Tc(B) or Tm(W)-Tc(W) within the above range, it is possible to simultaneously contain an amorphous resin in addition to a crystalline resin and control it by the structure, amount ratio, molecular chain length, etc. of the crystalline resin and the amorphous resin. It is considered that this is because when the toner melted during fixing crystallizes, the amorphous resin enters the molecular arrangement of the crystalline resin and controls the crystallization speed. More specifically, it is easier to control Tm(B)-Tc(B) within the above range by making the structure and molecular chain length of the crystalline resin and the amorphous resin closer to each other and by setting the content of the amorphous resin to a preferred content described later. It is also considered that the above means for controlling Tm(B)-Tc(B) makes it easier to control Tm(W)-Tc(W) within the above range due to the interaction between the resin and the release agent.
[0025] From the viewpoint of low-temperature fixability, the content of the crystalline resin in the binder resin is preferably 25.0% by mass or more, and more preferably 35.0% by mass or more. The amount of the crystalline resin in the binder resin is preferably 25.0 to 95.0% by mass, more preferably 35.0 to 80.0% by mass, even more preferably 50.0 to 75.0% by mass, and even more preferably 65.0 to 75.0% by mass.
[0026] In order to control Tm(B)-Tc(B) and Tm(W)-Tc(W) within the above range, the crystalline resin preferably contains a crystalline vinyl resin, and the amorphous resin preferably contains an amorphous vinyl resin. The crystalline resin is more preferably a crystalline vinyl resin, and the amorphous resin is more preferably an amorphous vinyl resin. The crystalline vinyl resin has a long-chain alkyl group as a side chain, and the long-chain alkyl groups of the side chains are oriented to each other to show crystallinity. This makes it easy for the side chain of the crystalline vinyl resin and the amorphous vinyl resin to get along and interact with each other, making it easy to control Tm(B)-Tc(B) within the above range. It is also considered that the above means for controlling Tm(B)-Tc(B) makes it easy to control Tm(W)-Tc(W) within the above range due to the interaction between the resin and the release agent.
[0027] From the viewpoint of controlling Tm(B)-Tc(B) and Tm(W)-Tc(W) within the above ranges, the crystalline resin more preferably contains a monomer unit represented by the following formula (1) (more preferably (1-1)). It is more preferable that the crystalline resin contains a monomer unit having a lactam structure, and it is even more preferable that the crystalline resin contains a monomer unit having a lactam structure of a five-membered ring. It is even more preferable that the monomer unit having a lactam structure is represented by the following formula (L) (more preferably formula (L-1)). It is believed that when the crystalline resin has a lactam structure, the crystalline resin has a polar site, which makes it easier to interact with other materials such as polyfunctional ester wax. [ka]
[0028] In formula (1), R1 represents a hydrogen atom or a methyl group, L1 represents a single bond, an ester bond, or an amide bond (preferably an ester bond), and m represents an integer of 15 to 30 (preferably 17 to 29, more preferably 19 to 23). In formula (1-1), R3 represents a hydrogen atom or a methyl group, and R4 represents a linear alkyl group having 16 to 31 carbon atoms (preferably 18 to 28, more preferably 20 to 24). In formulae (L) and (L-1), R2 represents a hydrogen atom or a methyl group, and n is an integer of 1 to 4 (preferably 1 to 3).
[0029] Furthermore, the toner contains a release agent, and Tm(W)-Tc(W) represents the crystallization rate of the release agent. The present inventors have found that in order to obtain the above effect, it is necessary to control not only the crystallization rate of the crystalline resin but also the crystallization rate of the release agent. The inventors have found that good color reproducibility can be obtained by setting Tm(W)-Tc(W) to 15.0°C or higher. This is believed to be because, as explained in the case of Tm(B)-Tc(B), the melt viscosity of a multi-color image increases after the colors are thoroughly mixed during fixing. The inventors have also found that the gloss uniformity of a fixed image can be improved by setting Tm(W)-Tc(W) to 15.0°C or higher. This is believed to be because, as explained in the case of Tm(B)-Tc(B), the difference in volumetric shrinkage rate between areas with a large amount of toner and areas with a small amount of toner can be reduced.
[0030] In addition, the toner of the present disclosure has a Tm(W)-Tc(W) of 25.0°C or less. Tm(W)-Tc(W) is preferably 24.0°C or less. The present inventors have found that when Tm(W)-Tc(W) is in the above range, the gloss uniformity of the fixed image is improved. This is believed to be because, as in the above, the fixed image is prevented from being affected by the unevenness of the paper and becoming non-uniform in gloss. Tm(W)-Tc(W) is preferably 19.0 to 24.0°C, more preferably 20.0 to 24.0°C. Tm(W) is preferably 60.0 to 85.0°C, and more preferably 70.0 to 80.0°C. Tc(W) is preferably 40.0 to 60.0°C, and more preferably 47.0 to 57.0°C.
[0031] It is possible to control Tm(B)-Tc(B) and Tm(W)-Tc(W) within the above ranges by adjusting the structure and mixing ratio of the crystalline resin and release agent, molecular chain length, etc. We believe this is because when the molten toner crystallizes, the crystalline resin and release agent form a eutectic mixture, making it possible to control the crystallization speed. The mixing ratio of the crystalline resin and the release agent varies depending on the substance used, and any amount can be selected. One method is to add the release agent in an amount that makes it easy to control the crystallization rate sufficiently. In addition, it is preferable to add the release agent in an amount described later so that the crystallization rate does not become too slow. In order to control Tm(B)-Tc(B) and Tm(W)-Tc(W) within the above ranges, it is preferable that the release agent contains a multifunctional ester wax. This is because multifunctional ester wax not only causes a single crystalline resin molecule to form a eutectic, but also exists between molecules in a bridge-like state, making it easier for the effect to be felt throughout the entire resin.
[0032] The polyfunctional ester wax refers to an ester compound of a polyhydric alcohol and a monocarboxylic acid, and an ester compound of a polycarboxylic acid and a monoalcohol. The polyfunctional ester wax is preferably at least one ester compound selected from the group consisting of an ester compound of a tetravalent to octavalent alcohol and an aliphatic monocarboxylic acid, and an ester compound of a tetravalent to octavalent carboxylic acid and an aliphatic monoalcohol. More preferably, the polyfunctional ester wax is at least one ester compound selected from the group consisting of an ester compound of a hexavalent to octavalent alcohol and an aliphatic monocarboxylic acid, and an ester compound of a hexavalent to octavalent carboxylic acid and an aliphatic monoalcohol.
[0033] In addition, in order to control Tm(B)-Tc(B) within the above range, when using a crystalline resin having a monomer unit of formula (1), it is preferable to simultaneously contain a straight-chain fatty acid metal salt. The straight-chain fatty acid metal salt is a salt of a metal other than sodium and potassium with a straight-chain fatty acid. In particular, with respect to the relationship with m in formula (1), when the carbon number of the straight-chain fatty acid of the straight-chain fatty acid metal salt is C(b), it is preferable that C(b) satisfies m-10≦C(b)≦m+10, more preferably satisfies m-6≦C(b)≦m+6, and even more preferably satisfies m-4≦C(b)≦m+4. In addition, it is preferable that the valence of the metal of the straight-chain fatty acid metal salt is divalent or more. That is, it is preferable that the straight-chain fatty acid metal salt is a salt of a divalent or more metal and a straight-chain fatty acid.
[0034] Satisfying m-10≦C(b)≦m+10 indicates that the chain length of the alkyl group in formula (1) is close to the chain length of the straight-chain fatty acid in the straight-chain fatty acid metal salt. In general, alkyl chains with similar chain lengths have a high affinity with each other. It is believed that by incorporating a straight-chain fatty acid metal salt having a chain length close to the chain length of the alkyl group in formula (1) that exhibits crystallinity, it is possible to create a eutectic-like state between the crystalline resin and the straight-chain fatty acid metal salt. Therefore, the crystallization rate can be controlled. Furthermore, fatty acid metal salts containing divalent or higher metals often have two or more alkyl chains, which makes them compatible with the alkyl chains of other crystalline resin molecules. As a result, when the toner melts in the fixing process and the molecular chains become mobile, the fatty acid metal salts introduced into the molecular chains of the crystalline resin are also introduced into the molecular chains of other crystalline resins, creating a pseudo-bridged state and exerting an effect on the entire resin.
[0035] In the present disclosure, the valence of the metal in the straight-chain fatty acid metal salt is divalent or higher means that the metal ion can have a valence of divalent or higher. There are no particular limitations on the divalent or higher metal. However, at least one selected from the group consisting of calcium and aluminum is preferred. Aluminum is preferred. The straight-chain fatty acid metal salt may be at least one selected from the group consisting of zinc octylate, magnesium distearate, aluminum distearate, calcium distearate, zinc distearate, calcium montanate, calcium laurate, barium laurate, calcium ricinoleate, barium ricinoleate, zinc ricinoleate, etc. It is more preferred that the straight-chain fatty acid metal salt contains aluminum distearate.
[0036] Furthermore, the toner satisfies Tc(W)≦Tm(B). By satisfying this, a toner excellent in color reproducibility and image gloss uniformity can be obtained. Tc(W)≦Tm(B) indicates that the crystallization temperature of the release agent is equal to or lower than the melting point of the crystalline resin. This indicates that there is a temperature range in which the release agent and the crystalline resin are both melted. In the toner of the present disclosure, the release agent and the crystalline resin interact with each other by forming a eutectic, so a temperature range in which both are melted is necessary, and it is considered necessary to satisfy Tc(W)≦Tm(B). It is considered that the color reproducibility and gloss uniformity are improved by the existence of a temperature range in which the release agent and the crystalline resin are both melted, because the crystalline resin and the release agent form a eutectic to control the crystallization speed. The above range can be satisfied by selecting the crystalline resin and release agent materials and designing the resin such as the molecular weight. Tm(B)-Tc(W) is preferably 0.0 to 26.0°C, more preferably 5.0 to 25.0°C, and further preferably 10.0 to 20.0°C.
[0037] Furthermore, in differential scanning calorimetry of the toner, after obtaining differential scanning calorimetry curve B, the toner is kept at 10°C for 10 minutes, and then heated from 10°C to 180°C at a heating rate of 10°C / min to obtain differential scanning calorimetry curve C. At this time, it is preferable that differential scanning calorimetry curve C has an endothermic peak (B2) derived from the crystalline resin. When the peak temperature (°C) of the endothermic peak (B2) is Tm(B2), it is preferable that Tm(B) and Tm(B2) satisfy 1.0≦Tm(B)-Tm(B2)≦10.0.
[0038] The fact that Tm(B)-Tm(B2) is in the above range indicates that Tm(B), i.e., the melting point corresponding to the toner before fixing, is higher than the melting point corresponding to the toner after fixing. By having Tm(B)-Tm(B2) in the above range, the balance between low-temperature fixability and heat-resistant storage stability becomes particularly good. Tm(B)-Tm(B2) is more preferably 4.0 to 10.0°C. Tm(B)-Tm(B2) can be increased by promoting crystallization through heat treatment near the crystallization temperature of the crystalline resin during toner production.Tm(B)-Tm(B2) can also be decreased by suppressing crystallization by heating the crystalline resin to a temperature equal to or higher than the crystallization temperature during toner production and then rapidly cooling it.
[0039] Furthermore, the toner of the present disclosure has a storage elastic modulus G'(TmB) of 1.0×10 5 ~1.0×10 8 Pa. G'(TmB) represents the storage modulus of the toner near the melting point of the crystalline resin. A toner having a storage modulus in this range retains a certain degree of elasticity near the melting point, and the problems of the present disclosure are likely to occur. G'(TmB) is 1.0×10 5 If the pressure is less than 1.0×10 Pa, the paper unevenness will affect the gloss uniformity. 8 If it exceeds this value, the low-temperature fixability is liable to decrease.
[0040] G'(TmB) is preferably 1.0 x 10 6 ~6.0×10 7Pa, more preferably 3.0×10 6 ~1.0×10 7 It is Pa. G'(TmB) can be increased by, for example, reducing the amount of crystalline resin added, increasing the molecular weight of the binder resin, or adding a crosslinking agent. G'(TmB) is also It can be reduced by, for example, increasing the amount of crystalline resin added or reducing the molecular weight of the binder resin.
[0041] The crystalline resin will be described below. As described above, in the present disclosure, the crystalline resin refers to a resin that shows a clear endothermic peak in a differential scanning calorimeter (DSC) measurement. Examples of the crystalline resin include vinyl resins, polyester resins, polyurethane resins, and epoxy resins having crystallinity, with vinyl resins having crystallinity being preferred.
[0042] The crystalline resin preferably contains 30.0% by mass or more of the monomer unit (hereinafter also referred to as monomer unit (a)) represented by the above formula (1). Formula (1) indicates that the crystalline resin has a long-chain alkyl group, and when the crystalline resin has a long-chain alkyl group, the resin is more likely to exhibit crystallinity. The crystalline resin preferably contains 30.0 to 90.0% by mass of the monomer unit (a) represented by formula (1), more preferably 60.0 to 90.0% by mass, and even more preferably 75.0 to 90.0% by mass. In formula (1), m represents an integer of 15 to 30. When m is 15 to 30, the crystalline resin is more likely to exhibit crystallinity, and a toner having excellent low-temperature fixing ability can be obtained. m is preferably 17-29, and more preferably 19-23.
[0043] As a method for introducing the monomer unit (a), there is a method of polymerizing the following (meth)acrylic acid esters. For example, (meth)acrylic acid esters having a linear alkyl group having 16 to 36 carbon atoms [stearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosanyl (meth)acrylate, behenyl (meth)acrylate, lignoceryl (meth)acrylate, ceryl (meth)acrylate, octacosyl (meth)acrylate, myricyl (meth)acrylate, dotriacontyl (meth)acrylate, etc.] and (meth)acrylic acid esters having a branched alkyl group having 18 to 36 carbon atoms [2-decyltetradecyl (meth)acrylate, etc.] can be mentioned.
[0044] When the crystalline resin is a vinyl resin having crystallinity, it is possible to have other monomer units in addition to the monomer unit (a). As a method for introducing other monomer units, there is a method of polymerizing the (meth)acrylic acid ester and other vinyl monomers. The other monomer units may be used alone or in combination of two or more.
[0045] Other vinyl monomers include the following: (meth)acrylic acid esters such as styrene, α-methylstyrene, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. Monomer having a urea group: for example, a monomer obtained by reacting an amine having 3 to 22 carbon atoms [primary amine (such as normal butylamine, t-butylamine, propylamine, and isopropylamine), secondary amine (such as di-normal ethylamine, di-normal propylamine, and di-normal butylamine), aniline, and cycloxylamine] with an isocyanate having 2 to 30 carbon atoms and an ethylenically unsaturated bond by a known method. Monomers having a carboxy group; for example, methacrylic acid, acrylic acid, 2-carboxyethyl (meth)acrylate, etc. Monomers having a hydroxy group; for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, etc. Monomers having an amide group; for example, acrylamide, amines having 1 to 30 carbon atoms and carboxylic acids having 2 to 30 carbon atoms having an ethylenically unsaturated bond (acrylic acid, methacrylic acid, etc.) ) by a known method. Monomers having a lactam structure; for example, N-vinyl-2-pyrrolidone.
[0046] Among them, it is preferable to use a monomer having a lactam structure, and more preferably the lactam structure has a 5-membered ring. It is preferable to use N-vinyl-2-pyrrolidone as the monomer having a 5-membered ring lactam structure. The monomer unit having a lactam structure is exemplified by the monomer unit represented by the above formula (L) (preferably formula (L-1)). The crystalline resin preferably contains the monomer unit represented by formula (L) (preferably formula (L-1)) in an amount of 1.0 to 15.0% by mass, more preferably 4.0 to 10.0% by mass. The crystalline resin may contain a styrene monomer unit, and the crystalline resin preferably contains the styrene monomer unit in an amount of 1.0 to 25.0 mass %, and more preferably 7.0 to 15.0 mass %. The crystalline resin may contain a monomer unit based on (meth)acrylic acid. The crystalline resin preferably contains 0.5 to 5.0 mass % of the monomer unit based on (meth)acrylic acid, and more preferably contains 1.5 to 4.0 mass %.
[0047] When the crystalline resin is a polyester resin, a resin exhibiting crystallinity can be used among polyester resins obtainable by reaction of a divalent or higher polyvalent carboxylic acid with a polyhydric alcohol.
[0048] Examples of polycarboxylic acids include the following compounds: Examples of the dibasic acids include succinic acid, adipic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, malonic acid, and dodecenylsuccinic acid, and their anhydrides or lower alkyl esters, as well as aliphatic unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, and citraconic acid. Other examples include 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, and anhydrides or lower alkyl esters thereof. These may be used alone or in combination of two or more.
[0049] Examples of the polyhydric alcohol include the following compounds: Examples of the alkylene glycol include alkylene glycols (ethylene glycol, 1,2-propylene glycol, and 1,3-propylene glycol); alkylene ether glycols (polyethylene glycol and polypropylene glycol); alicyclic diols (1,4-cyclohexanedimethanol); bisphenols (bisphenol A); and alkylene oxide (ethylene oxide and propylene oxide) adducts of alicyclic diols. The alkyl moieties of the alkylene glycols and alkylene ether glycols may be linear or branched. Further examples include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, etc. These may be used alone or in combination of two or more.
[0050] For the purpose of adjusting the acid value or hydroxyl value, monovalent acids such as acetic acid and benzoic acid, and monovalent alcohols such as cyclohexanol and benzyl alcohol can also be used as necessary. The method for producing the polyester resin is not particularly limited, and for example, a transesterification method or a direct polycondensation method can be used alone or in combination.
[0051] The binder resin contains a non-crystalline resin in addition to a crystalline resin. Examples of the non-crystalline resin include vinyl resin, polyester resin, polyurethane resin, and epoxy resin. Amorphous vinyl resins such as polystyrene are preferred.
[0052] Examples of vinyl monomers include the following: (meth)acrylic acid esters such as styrene, α-methylstyrene, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. Monomer having a urea group: for example, a monomer obtained by reacting an amine having 3 to 22 carbon atoms [primary amine (such as normal butylamine, t-butylamine, propylamine, and isopropylamine), secondary amine (such as di-normal ethylamine, di-normal propylamine, and di-normal butylamine), aniline, and cycloxylamine] with an isocyanate having 2 to 30 carbon atoms and an ethylenically unsaturated bond by a known method. Monomers having a carboxy group; for example, methacrylic acid, acrylic acid, 2-carboxyethyl (meth)acrylate, etc. Monomers having a hydroxy group; for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, etc. Monomers having an amide group; for example, acrylamide, monomers obtained by reacting an amine having 1 to 30 carbon atoms with a carboxylic acid having 2 to 30 carbon atoms (such as acrylic acid and methacrylic acid) having an ethylenically unsaturated bond by a known method, and the like.
[0053] Among these, it is preferable to use styrene, (meth)acrylic acid, methyl (meth)acrylate, and t-butyl (meth)acrylate.The amorphous vinyl resin preferably contains a monomer unit based on styrene.
[0054] The content of the amorphous resin in the binder resin is preferably 5.0 to 75.0 mass %, more preferably 5.0 to 50.0 mass %, even more preferably 20.0 to 50.0 mass %, and even more preferably 25.0 to 35.0 mass %.
[0055] The binder resin may contain a crosslinking agent as necessary. Examples of the crosslinking agent that can be used include, but are not limited to, the following compounds: Ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate, neopentyl glycol dimethacrylate, neopentyl glycol diacrylate, divinylbenzene, bis(4-acryloxypolyethoxyphenyl)propane, ethylene glycol diacrylate, 1,3-butylene glycol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol #200, #400, #600 diacrylates, dipropylene glycol diacrylate, polypropylene glycol diacrylate and polyester diacrylate (MANDA Nippon Kayaku), as well as the above acrylates replaced with methacrylates. The content of the crosslinking agent in the binder resin is preferably from 0.01 to 10.00% by mass, and more preferably from 0.03 to 5.00% by mass.
[0056] The toner contains a release agent. Examples of the release agent include a hydrocarbon wax and an ester wax. The release agent preferably contains a polyfunctional ester wax.
[0057] The hydrocarbon wax is not particularly limited, but examples thereof include the following: Aliphatic hydrocarbon waxes: low molecular weight polyethylene, low molecular weight polypropylene, low molecular weight olefin copolymer, Fischer-Tropsch wax, or waxes obtained by oxidizing or adding an acid to these.
[0058] The ester wax may be any wax having at least one ester bond in one molecule, and may be either a natural ester wax or a synthetic ester wax. The ester wax is not particularly limited, but examples thereof include the following. Esters of monohydric alcohols and monocarboxylic acids, such as behenyl behenate, stearyl stearate, and palmityl palmitate; esters of dihydric carboxylic acids and monoalcohols, such as dibehenyl sebacate; esters of dihydric alcohols and monocarboxylic acids, such as ethylene glycol distearate and hexanediol dibehenate; esters of trihydric alcohols and monocarboxylic acids, such as glycerin tribehenate; esters of tetrahydric alcohols and monocarboxylic acids, such as pentaerythritol tetrastearate and pentaerythritol tetrapalmitate; esters of hexahydric alcohols and monocarboxylic acids, such as dipentaerythritol hexastearate, dipentaerythritol hexapalmitate, and dipentaerythritol hexabehenate; esters of polyfunctional alcohols and monocarboxylic acids, such as polyglycerin behenate; natural ester waxes, such as carnauba wax and rice wax.
[0059] Among them, at least one selected from the group consisting of esters of hexahydric alcohols and monocarboxylic acids such as dipentaerythritol hexastearate, dipentaerythritol hexapalmitate, dipentaerythritol hexabehenate, etc. More preferably, the release agent contains dipentaerythritol hexastearate. As the release agent, a hydrocarbon wax or an ester wax may be used alone, or a hydrocarbon wax and an ester wax may be used in combination, or two or more of each may be mixed and used.
[0060] In the toner, the content of the release agent in the toner particles is preferably 1.0 to 30.0% by mass, more preferably 2.0 to 25.0% by mass, further preferably 5.0 to 15.0% by mass, and even more preferably 6.0 to 13.0% by mass. When the content of the release agent in the toner particles is within the above range, the above-mentioned eutectic effect with the crystalline resin is easily exhibited.
[0061] The melting point of the release agent is preferably 60 to 120° C. When the melting point of the release agent is in the above range, the release agent melts during fixing and easily seeps out onto the toner particle surface, and the release property is easily exhibited. The melting point of the release agent is more preferably 70 to 100° C.
[0062] The toner may contain a colorant. Examples of the colorant include known organic pigments, organic dyes, inorganic pigments, carbon black as a black colorant, magnetic particles, etc. In addition, colorants that have been used in conventional toners may also be used. Examples of yellow colorants include condensed azo compounds, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Specifically, CI Pigment Yellow 12, 13, 14, 15, 17, 62, 74, 83, 93, 94, 95, 109, 110, 111, 128, 129, 147, 155, 168, and 180 are preferably used.
[0063] Magenta colorants include the following: condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Specific examples include CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 166, 169, 177, 184, 185, 202, 206, 220, 221, and 254 are preferably used. Examples of cyan colorants include copper phthalocyanine compounds and their derivatives, anthraquinone compounds, and basic dye lake compounds. Specifically, CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66 are preferably used.
[0064] The colorant is selected in consideration of hue angle, chroma, brightness, light resistance, transparency on an OHP sheet, and dispersibility in the toner. The content of the colorant is preferably 1.0 to 20.0 parts by mass with respect to 100.0 parts by mass of the binder resin. When magnetic particles are used as the colorant, the content is preferably 40.0 to 150.0 parts by mass with respect to 100.0 parts by mass of the binder resin.
[0065] If necessary, a charge control agent may be contained in the toner particles. Alternatively, the charge control agent may be added externally to the toner particles. By blending the charge control agent, it becomes possible to stabilize the charge characteristics and control the amount of triboelectric charge optimally according to the development system. Any known charge control agent can be used as the charge control agent, and a charge control agent that can charge quickly and stably maintain a constant charge amount is particularly preferred.
[0066] As the charge control agent that controls the toner to have a negative charge, the following can be mentioned. Organometallic compounds and chelate compounds are effective, and examples thereof include monoazo metal compounds, acetylacetone metal compounds, aromatic oxycarboxylic acids, aromatic dicarboxylic acids, oxycarboxylic acids and dicarboxylic acid-based metal compounds. The following can be mentioned as the substances that control the toner to have a positive charge. Examples of the organic solvent include nigrosine, quaternary ammonium salts, metal salts of higher fatty acids, diorgano tin borates, guanidine compounds, and imidazole compounds. The content of the charge control agent is preferably 0.01 to 20.0 parts by mass, and more preferably 0.5 to 10.0 parts by mass, relative to 100.0 parts by mass of the toner particles.
[0067] The toner particles may be used as they are as a toner, or may be mixed with an external additive, if necessary, and attached to the surface of the toner particles to form a toner. The external additive may be an inorganic fine particle selected from the group consisting of silica fine particles, alumina fine particles, and titania fine particles, or a composite oxide thereof, etc. Examples of the composite oxide include silica aluminum fine particles and strontium titanate fine particles. The content of the external additive is preferably 0.01 to 8.0 parts by mass, and more preferably 0.1 to 4.0 parts by mass, relative to 100 parts by mass of the toner particles.
[0068] The toner particles may be produced by any conventional method, such as suspension polymerization, emulsion aggregation, dissolution suspension, or pulverization, as long as the method falls within the scope of the present invention. It is preferable to produce the toner particles by suspension polymerization.
[0069] The suspension polymerization method will now be described in detail. For example, a polymerizable monomer composition is prepared by mixing previously synthesized crystalline resin, polymerizable monomers for forming an amorphous resin, a release agent, and, if necessary, other materials such as a colorant and a charge control agent, and dissolving or dispersing them uniformly. The polymerizable monomer composition is then dispersed in an aqueous medium using a stirrer or the like to prepare suspended particles of the polymerizable monomer composition, and the polymerizable monomer contained in the particles is then polymerized using an initiator or the like to obtain toner particles. After the polymerization is completed, the toner particles are filtered, washed and dried by known methods, and external additives are added as necessary to obtain the toner.
[0070] As the polymerization initiator, a known polymerization initiator can be used. Examples of the polymerization initiator include azo or diazo polymerization initiators such as 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile, and azobisisobutyronitrile; and peroxide polymerization initiators such as benzoyl peroxide, t-butyl peroxy 2-ethylhexanoate, t-butyl peroxypivalate, t-butyl peroxyisobutyrate, t-butyl peroxyneodecanoate, methyl ethyl ketone peroxide, diisopropyl peroxycarbonate, cumene hydroperoxide, 2,4-dichlorobenzoyl peroxide, and lauroyl peroxide. Furthermore, the molecular weight may be adjusted using a known chain transfer agent or polymerization inhibitor.
[0071] The aqueous medium may contain an inorganic or organic dispersion stabilizer. As the dispersion stabilizer, known dispersion stabilizers can be used. Examples of inorganic dispersion stabilizers include phosphates such as hydroxyapatite, tricalcium phosphate, dicalcium phosphate, magnesium phosphate, aluminum phosphate, and zinc phosphate; carbonates such as calcium carbonate and magnesium carbonate; metal hydroxides such as calcium hydroxide, magnesium hydroxide, and aluminum hydroxide; sulfates such as calcium sulfate and barium sulfate; calcium metasilicate; bentonite; silica; and alumina.
[0072] On the other hand, examples of organic dispersion stabilizers include polyvinyl alcohol, gelatin, methyl cellulose, methylhydroxypropyl cellulose, ethyl cellulose, sodium salt of carboxymethyl cellulose, polyacrylic acid and its salts, and starch.
[0073] When an inorganic compound is used as the dispersion stabilizer, a commercially available product may be used as it is, but in order to obtain finer particles, the inorganic compound may be formed in an aqueous medium and then used. For example, in the case of calcium phosphates such as hydroxyapatite or tricalcium phosphate, an aqueous solution of the phosphate may be mixed with an aqueous solution of the calcium salt under high agitation.
[0074] The aqueous medium may contain a surfactant. As the surfactant, a known surfactant can be used. For example, anionic surfactants such as sodium dodecylbenzene sulfate and sodium oleate, cationic surfactants, amphoteric surfactants, nonionic surfactants, etc. can be mentioned.
[0075] The calculation and measurement methods for various physical properties are described below. <Differential scanning calorimetry (DSC) measurement method> The endothermic peak temperatures and exothermic peak temperatures (Tm(B), Tm(W), Tc(B), Tc(W) and Tm(B2)) of the crystalline resin and release agent are measured using a differential scanning calorimeter "Q1000" (manufactured by TA Instruments) in accordance with ASTM D3418-82. The melting points of indium and zinc are used for temperature correction of the detector, and the heat of fusion of indium is used for heat correction.
[0076] Toner measurements are performed by first weighing out 10 mg of toner and placing it in an aluminum pan, with an empty aluminum pan used as a reference. In the first temperature rise process, measurements are performed while the measurement sample is heated from 20°C to 180°C at 10°C / min, to obtain differential scanning calorimetric curve A. After that, the sample is held at 180°C for 10 minutes, and then cooled from 180°C to 10°C at 10°C / min, during which measurements are performed, to obtain differential scanning calorimetric curve B. Furthermore, at 10°C, After holding for 10 minutes, in the second heating process, the temperature is again raised from 10°C to 180°C at 10°C / min while performing measurements, to obtain a differential scanning calorimetric curve C. The peak top temperature appearing in the obtained differential scanning calorimetric curve is determined and regarded as the peak temperature.
[0077] In addition, by separating the crystalline resin and the release agent from the toner by the procedure described below and measuring the crystalline resin or the release agent separately by DSC, it is possible to confirm whether the obtained peak is due to the crystalline resin or the release agent.
[0078] <Method for measuring storage modulus G'(TmB)> The storage modulus G' (TmB) is measured using a viscoelasticity measuring device (rheometer) ARES (manufactured by Rheometrics Scientific). The outline of the measurement is described in the ARES Operation Manuals 902-30004 (August 1997 edition) and 902-00153 (July 1993 edition) published by Rheometrics Scientific, and is as follows. Measurement tool: torsion rectangular Measurement sample: For the toner, a rectangular parallelepiped sample with a width of 12 mm, height of 20 mm, and thickness of 2.5 mm is prepared using a pressure molding machine (maintain 25 kN for 30 minutes at room temperature). The pressure molding machine used is the 100 kN press NT-100H manufactured by NPa Systems. Leave the jig and sample at room temperature (23°C) for 1 hour, then attach the sample to the jig. See Figure 1. As shown in the figure, fix the sample so that the width of the measurement area is 12.0 mm, the thickness is 2.5 mm, and the height is 10.0 mm. After regulating the temperature to 30°C for 10 minutes, perform the measurement with the following settings. ·Measurement frequency: 6.28rad / s Measurement distortion setting: Set the initial value to 0.1% and perform the measurement in automatic measurement mode. - Sample elongation correction: Adjusted in automatic measurement mode Measurement temperature: 30℃ to 150℃ at a rate of 2℃ per minute Measurement interval: Measure viscoelastic data every 30 seconds, i.e., every 1°C. Data is transferred via an interface to RSI Orchestrator (control, data acquisition and analysis software) (manufactured by Rheometrics Scientific) running on Microsoft Windows 2000. Among the measurement data, the storage modulus G' at Tm(B)° C. determined by the above-mentioned DSC measurement is read, and G'(TmB) is calculated.
[0079] <Method of separating toner particles from a toner> When analyzing toner particles, if the surfaces of the toner particles have been treated with an external additive or the like, the external additive is separated by the following method to obtain toner particles. Add 160 g of sucrose (Kishida Chemical) to 100 mL of ion-exchanged water and dissolve in a hot water bath to prepare a concentrated sucrose solution. Place 31 g of the concentrated sucrose solution and 6 mL of Contaminon N (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) in a centrifuge tube to prepare a dispersion. Add 1.0 g of toner to this dispersion and break up any toner clumps with a spatula or similar. Shake the centrifuge tube with a shaker at 350 strokes per minute (spm) for 20 minutes. After shaking, transfer the solution to a glass tube (50 mL) for a swing rotor and separate in a centrifuge at 3,500 rpm for 30 minutes. This operation separates the toner particles from the detached external additives. Visually check that the toner and the aqueous solution are sufficiently separated, and collect the toner that has separated to the top layer with a spatula. The collected toner is filtered through a vacuum filter, and then dried in a dryer for at least one hour to obtain toner particles. This operation is repeated several times to ensure the required amount.
[0080] <Method of measuring molecular weight> The molecular weight, such as the weight average molecular weight Mw, is measured by gel permeation chromatography (GPC) as follows. First, the sample is dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. The resulting solution is then filtered through a solvent-resistant membrane filter "Myshoridisc" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution is adjusted so that the concentration of components soluble in THF is 0.8 mass%. This sample solution is used to perform measurements under the following conditions. Equipment: HLC8120 GPC (detector: RI) (Tosoh Corporation) Column: 7 columns of Shodex KF-801, 802, 803, 804, 805, 806, 807 (Showa Denko Co., Ltd.) Eluent: Tetrahydrofuran (THF) ·Flow rate: 1.0ml / min Oven temperature: 40.0℃ Sample injection volume: 0.10ml In calculating the molecular weight of the sample, a molecular weight calibration curve prepared using standard polystyrene resins (e.g., trade names "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500" manufactured by Tosoh Corporation) is used.
[0081] <Method for separating crystalline resin from toner particles> The crystalline resin can be separated from the toner by a known method, one example of which is shown below. Gradient polymer LC is used as a method for separating resin components from toner. This analysis allows separation according to the polarity of the resin in the binder resin, regardless of the molecular weight.
[0082] First, the toner is dissolved in chloroform. The sample concentration is adjusted to 0.1% by mass in chloroform, and the solution is filtered through a 0.45 μm PTFE filter before being used for measurement. The measurement conditions for gradient polymer LC are shown below. Equipment: UlTIMATE3000 (Thermo Fisher Scientific) Mobile phase: A Chloroform (HPLC), B Acetonitrile (HPLC) Gradient: 2min (A / B=0 / 100) → 25min (A / B=100 / 0) (Note that the gradient of the change in the mobile phase was made linear.) Flow rate: 1.0mL / min Injection: 0.1% by mass x 20μL Column: Tosoh TSKgel ODS (4.6mmφx150mm x 5μm) Column temperature: 40℃ Detector: Corona Charged Aerosol Detector (Corona-CAD) (Thermo Fisher Scientific)
[0083] The time-intensity graph obtained from the measurement shows that the resin components can be separated into two peaks depending on the polarity. After that, the above measurement is carried out again, and by taking fractions at the time when each peak reaches its valley, it is possible to separate the two types of resin. The separated resins are subjected to DSC measurement, and resins that have a melting point peak are classified as crystalline resins, and resins that do not have a melting point peak are classified as amorphous resins.
[0084] The release agent in the toner is separated by recycling HPLC to separate components having a molecular weight of 3000 or less as the release agent. The measurement method is shown below. First, a chloroform solution of the toner is prepared by the method described above. The obtained solution is then filtered through a solvent-resistant membrane filter "Myshoridisc" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution is adjusted so that the concentration of components soluble in chloroform is 1.0 mass %. This sample solution is used to perform measurements under the following conditions. ·Equipment: LC-Sakura NEXT (manufactured by Nippon Analytical Industry Co., Ltd.) Column: JAIGEL 2H, 4H (Japan Analytical Industry Co., Ltd.) Eluent: Chloroform ·Flow rate: 10.0ml / min Oven temperature: 40.0℃ Sample injection volume: 1.0ml In calculating the molecular weight of the sample, a molecular weight calibration curve prepared using standard polystyrene resins (e.g., trade names "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500" manufactured by Tosoh Corporation) is used. From the molecular weight curve thus obtained, components having a molecular weight of 3000 or less are repeatedly separated to remove the release agent from the toner. Note that the molecular weight to be separated can be changed in consideration of the molecular weight of the release agent.
[0085] <Method of measuring the content of various monomer units such as monomer unit (a) in a resin and the number of carbon atoms in the alkyl group> The content of the monomer unit (a) in the resin and the number of carbon atoms in the alkyl group are measured by 1 The measurement is performed by H-NMR under the following conditions. The crystalline resin separated by the above-mentioned method can be used as the measurement sample. Measuring device: FT NMR device JNM-EX400 (manufactured by JEOL Ltd.) Measurement frequency: 400MHz Pulse condition: 5.0μs Frequency range: 10500Hz Number of times: 64 Measurement temperature: 30℃ Sample: 50 mg of the measurement sample is placed in a sample tube with an inner diameter of 5 mm, deuterated chloroform (CDCl3) is added as a solvent, and this is dissolved in a thermostatic bath at 40°C to prepare the sample. Obtained 1 The H-NMR chart is analyzed to identify the structure of each monomer unit. As an example, the measurement of the content ratio of monomer unit (a) in a crystalline resin and the number of carbon atoms in the alkyl group is described here. Obtained 1In the H-NMR chart, a peak that is independent of the peaks attributable to the components of the monomer unit (a) is selected from the peaks attributable to the components of the other monomer units, and the integral value S1 of this peak is calculated. The integral values of the other monomer units contained in the crystalline resin are also calculated in the same manner.
[0086] When the monomer units constituting the crystalline resin are the monomer unit (a) and one other monomer unit, the content of the monomer unit (a) is calculated using the above integral value S1 and the integral value S2 of the peak of the other monomer unit as follows: where n1 and n2 are the numbers of hydrogen atoms in the constituent elements to which the peaks of interest for each site belong. Content of monomer unit (a) (mol%)= {(S1 / n1) / ((S1 / n1)+(S2 / n2))}×100 Even when two or more types of other monomer units are present, the content of the monomer unit (a) can be calculated in the same manner (using S3···Sx, n3···nx). The number of carbon atoms in the alkyl group is 1 It can be calculated from the integral ratio of the proton peak in the H-NMR chart.
[0087] In addition, when a polymerizable monomer that does not contain a hydrogen atom in any component other than the vinyl group is used, 13 Measure nuclei using C-NMR 13 C, and the measurement was performed in single pulse mode. 1 Calculation is performed in the same manner using H-NMR. In addition, the measurement results of infrared absorption spectrum (IR) and gas chromatography-mass spectrometry (GC-MS) may be used as necessary.
[0088] <Measurement of the content of crystalline resin in toner> In the method for separating the crystalline resin from the toner particles described above, the content of the crystalline resin in the toner is calculated based on the mass of the toner before it is dissolved in chloroform and the mass of the crystalline resin separated from the toner particles.
[0089] <Method for separating fatty acid metal salt from toner particles> 10.0 g of toner particles from which the external additives have been separated are weighed out, placed in a cylindrical filter paper (Toyo Roshi No. 84) and subjected to a Soxhlet extractor. 200 mL of tetrahydrofuran (THF) is added as a solvent and extraction is performed for 20 hours, and the THF-insoluble matter remaining on the cylindrical filter paper is dried to solidify. The obtained THF-insoluble matter is placed again in the cylindrical filter paper and subjected to a Soxhlet extractor. 200 mL of chloroform is added as a solvent and extraction is performed for 8 hours. The extract is concentrated and dried to separate the fatty acid metal salt from the toner particles. The operation is repeated as necessary to obtain the required amount of fatty acid metal salt.
[0090] <Measurement of the carbon number of straight-chain fatty acids in straight-chain fatty acid metal salts> After the fatty acid metal salt is extracted by the above-mentioned method, the carbon number is measured by the same method as the above-mentioned method for measuring the carbon number of the alkyl group.
[0091] <Identification of the metal valence of straight chain fatty acid metal salts> After the fatty acid metal salts are extracted by the above-mentioned method, the types of metals contained in the straight-chain fatty acid metal salts are analyzed using an inductively coupled plasma atomic emission spectrometer (ICP-AES (manufactured by Seiko Instruments Inc.)). As a pretreatment, 100.0 mg of fatty acid metal salt was added to 60% nitric acid (Kanto Chemical, atomic absorption spectrometry) Acid decomposition is performed by adding 8.00 ml of 100% ethanol (for use in fatty acid metal salts) to the solution. During acid decomposition, the solution is treated in a sealed container at an internal temperature of 220°C for 1 hour using a microwave high-power sample pretreatment device ETHOS1600 (Milestone General Co., Ltd.) to prepare a polyvalent metal element-containing solution sample. Ultrapure water is then added to a total of 50.00 g to prepare a measurement sample. A calibration curve is created for each metal element, the type of metal contained in the fatty acid metal salt is identified, and the valence of the metal is determined from the type. In the present disclosure, the valence of the metal in the linear fatty acid metal salt is divalent or higher refers to a metal species in which the metal ion can have a valence of divalent or higher. EXAMPLES
[0092] The present disclosure will be specifically described below with reference to examples, but these are not intended to limit the present disclosure in any way. In the following formulations, parts are by weight unless otherwise specified.
[0093] (Preparation of Crystalline Resin 1) The following materials were placed in a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere. Toluene 100.0 parts Monomer composition 100.0 parts (The monomer composition is a mixture of the following monomers in the ratio shown below.) (Docosyl acrylate (monomer (a)) 80.0 parts) (10.0 parts styrene) (N-vinyl-2-pyrrolidone 7.0 parts) (Methacrylic acid 3.0 parts) Polymerization initiator: 0.5 parts t-butyl peroxypivalate (NOF Corp.: Perbutyl PV) The inside of the reaction vessel was heated to 70°C while stirring at 200 rpm, and polymerization reaction was carried out for 12 hours, to obtain a solution in which the polymer of the monomer composition was dissolved in toluene. Then, the temperature of the solution was lowered to 25°C, and the solution was poured into 1000.0 parts of methanol while stirring, to precipitate the methanol insoluble matter. The obtained methanol insoluble matter was filtered, washed with methanol, and then vacuum dried at 40°C for 24 hours to obtain crystalline resin 1.
[0094] (Preparation of Crystalline Resins 2 to 7) Crystalline resins 2 to 7 were prepared in the same manner as in the preparation of crystalline resin 1, except that the monomer composition and the type and amount of polymerization initiator added were changed as shown in Table 1.
[0095] [Table 1] Mw indicates the weight average molecular weight.
[0096] (Preparation of Crystalline Resin 8) 281 parts of decanedioic acid and 283 parts of 1,6-hexanediol were placed in a reaction vessel equipped with a stirrer, a thermometer, a cooling tube, and a nitrogen gas inlet tube. After replacing the atmosphere in the reaction vessel with dry nitrogen gas, 0.1 parts of Ti(OBu)4 was added, and the reaction was carried out with stirring at about 180°C for 8 hours under a nitrogen gas flow. Furthermore, 0.2 parts of Ti(OBu)4 was added, the temperature was raised to about 220°C, and stirring was continued for 6 hours. After the reaction, the pressure inside the reaction vessel was reduced to 1333.2 Pa, and the reaction was carried out under reduced pressure to obtain a crystalline polyester resin, Crystalline Resin 8. Crystalline Resin 8 had a number average molecular weight (Mn) of 5500, a weight average molecular weight (Mw) of 18000, and a melting point of 67°C.
[0097] <Example 1> [Toner production by suspension polymerization method] (Production of toner particles 1) Styrene 30.0 parts Colorant: Copper phthalocyanine (CI Pigment Blue 15:3: manufactured by Dainichi Seika Chemicals Co., Ltd.) 6.5 parts A mixture of the above materials was prepared. The mixture was placed in an attritor (manufactured by Nippon Coke Corporation) and dispersed at 200 rpm for 2 hours using zirconia beads with a diameter of 5 mm to obtain a raw material dispersion.
[0098] On the other hand, 735.0 parts of ion-exchanged water and 16.0 parts of trisodium phosphate (12-hydrate) were added to a container equipped with a high-speed stirring device homomixer (manufactured by Primix Corporation) and a thermometer, and the temperature was raised to 60 ° C. while stirring at 12000 rpm. An aqueous calcium chloride solution in which 9.0 parts of calcium chloride (2-hydrate) was dissolved in 65.0 parts of ion-exchanged water was added thereto, and the mixture was stirred at 12000 rpm for 30 minutes while maintaining the temperature at 60 ° C. 10% hydrochloric acid was added thereto to adjust the pH to 6.0, and an aqueous medium in which an inorganic dispersion stabilizer containing hydroxyapatite was dispersed in water was obtained.
[0099] Next, the raw material dispersion liquid was transferred to a container equipped with a stirrer and a thermometer, and the temperature was raised to 60° C. while stirring at 100 rpm. ·Crystalline resin 1: 70.0 parts Release agent: 9.0 parts (Release agent: DP18 (dipentaerythritol hexastearate), melting point 79°C, manufactured by Nippon Seiro Co., Ltd.) Fatty acid metal salt (aluminum distearate) 0.5 parts The above materials were added thereto and stirred at 100 rpm for 30 minutes while maintaining the temperature at 60°C, and then 9.0 parts of t-butyl peroxypivalate (Perbutyl PV, manufactured by NOF Corp.) was added as a polymerization initiator and stirred for another minute. Then, the mixture was poured into the aqueous medium being stirred at 12000 rpm in the high-speed stirring device. Stirring was continued for 20 minutes at 12000 rpm in the high-speed stirring device while maintaining the temperature at 60°C, to obtain a granulation liquid.
[0100] The granulation liquid was transferred to a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube, and heated to 70° C. while stirring at 150 rpm under a nitrogen atmosphere. A polymerization reaction was carried out at 150 rpm for 12 hours while maintaining the temperature at 70° C., to obtain a toner particle dispersion liquid. The resulting toner particle dispersion was cooled to 45°C while stirring at 150 rpm, and then heat-treated for 5 hours while maintaining the temperature at 45°C. Dilute hydrochloric acid was then added while maintaining the stirring until the pH reached 1.5 to dissolve the dispersion stabilizer. The solid content was filtered off, thoroughly washed with ion-exchanged water, and vacuum-dried at 30°C for 24 hours to obtain toner particles 1.
[0101] (Preparation of Toner 1) For the above toner particles, 1:98.0 parts, silica fine particles (hydrophobized with hexamethyldisilazane, number-average particle size of primary particles: 10 nm, BET specific surface area: 170 m) were added as an external additive. 2 The mixture was mixed for 15 minutes at 3000 rpm using a Henschel mixer (manufactured by Nippon Coke Corporation) to obtain toner 1.
[0102] The physical properties of the obtained toner 1 are shown in Table 2. The results of evaluation by the toner evaluation method described later are shown in Table 3.
[0103] [Table 2] In the table, for example, 5×10^6 means 5×10 6 This indicates that.
[0104] [Table 3]
[0105] <Toner Evaluation Method> <1> Low temperature fixability The process cartridges filled with toners 1 to 21 and comparative toners 1 to 9 were left to stand for 48 hours at 25°C and 40% RH. Using an LBP-712Ci (Canon Inc.) modified so that it could operate even without the fixing unit, an unfixed image was printed out with an image pattern in which 9 square images of 10 mm x 10 mm were evenly arranged on the entire transfer paper. The amount of toner on the transfer paper was 0.80 mg / cm. 2 The fixing start temperature was evaluated. The transfer paper was A4 size paper ("Prover Bond paper": 105 g / m 2 (Fox River) was used. The fixing unit was an external fixing unit that had been removed from the LBP-712Ci and was designed to operate outside the laser beam printer. The fixing temperature of the external fixing unit was raised in 5°C increments from 90°C, and fixing was performed at a process speed of 260mm / sec. The fixed image was visually observed, and the lowest temperature at which no cold offset occurred was defined as the fixing start temperature, and the low-temperature fixing ability was evaluated according to the following criteria. The evaluation results are shown in Table 3. [Evaluation Criteria] A: Fixing start temperature is 100℃ or less B: Fixing start temperature is 105℃ or higher and 110℃ or lower C: Fixing start temperature is 115℃ or higher and 120℃ or lower D: Fixing start temperature exceeds 120°C
[0106] <2> Heat resistance / blocking resistance 10 g of toner was placed in a 100 mL resin cup and left for 7 days in an environment with a temperature of 45°C and a relative humidity of 95%, after which the degree of agglomeration was visually confirmed and the heat resistance storage stability was evaluated according to the following criteria. The evaluation results are shown in Table 3. (Evaluation Criteria) A: No aggregates were observed. B: Agglomerates are visible but easily disintegrate. C: Agglomerates are visible, but can be broken down by shaking. D: The aggregates can be grasped and do not easily crumble.
[0107] <3> Color reproducibility evaluation Color reproducibility was evaluated by the Japan Color inclusion rate, which is the width of the color gamut. The image forming device used was an LBP-712Ci, and images were formed and evaluated using cartridges provided with the product, except for the cyan cartridge. The printing environment was normal temperature and humidity (temperature 23°C, relative humidity 50%). The color gamut evaluation image used was the matching certification / proofing equipment / operation certification chart used in the Japan Color certification system. The printing was done using the ISO-compliant Japan Color 2011 for Sheet-fed Printing. The printing conditions are as follows: (Printing conditions) Printing paper: OKtop Coat 128 (Oji Paper Co., Ltd.) Print density: Yellow 1.35, Magenta 1.53, Cyan 1.55, Black 1.70 (Measurement conditions: after drying, Status E, black backing, absolute density (including paper white)) The amount of toner applied for each color was adjusted to achieve the above print density.
[0108] <Color gamut evaluation method and criteria for image samples> The evaluation of the image samples was carried out using X-Rite eXact (manufactured by X-Rite). Color measurement was carried out in accordance with the "ISO-compliant Japan Color 2011 for Sheet-fed Offset based on ISO12647-2 Manual". The measurement conditions are as follows: (Measurement conditions) Backing: White backing UV cut filter: None Incident / reflection method: 45 / 0 Observation light source: D50 Observation conditions: 2 degree viewing angle Lighting standard: M0 Using the above-mentioned device, the L * a * b * Chromaticity in the color system (L * , a * , b * ) was measured. * ) was calculated using the following formula based on the measured color characteristics. C * =((a * ) 2 +(b * ) 2 ) 1 / 2 The color gamut evaluation was performed by calculating the percentage of the color gamut obtained for each image for evaluating the color gamut that encompassed the Japan Color color gamut. <Japan Color Inclusion Rate Evaluation Criteria> A: 80% or more B: 75% or more but less than 80% C: 70% or more but less than 75% D: Less than 70%
[0109] <4> Evaluation of gloss uniformity the above <3> The fixed image of color reproducibility in the evaluation of 1) was used. The gloss value was measured using a handy gloss meter PG-1 (manufactured by Nippon Denshoku Industries Co., Ltd.). The measurement conditions were that the projection angle and reception angle were both set to 75°, and all image patterns with different toner loading amounts were measured. The standard deviation of these measured values was used to evaluate gloss uniformity. The evaluation results are shown in Table 3. [Gloss uniformity evaluation criteria] A: Gross standard deviation is 1.0 or less B: Gross standard deviation is greater than 1.0 and less than or equal to 2.0 C: Gross standard deviation is greater than 2.0 and less than or equal to 3.0 D: Gross standard deviation exceeds 3.0
[0110] <Examples 2 to 21 and Comparative Examples 1 to 9> Toner particles 2 to 21 and comparative toner particles 1 to 9 were obtained in the same manner as in Example 1, except that the materials used and the amounts added were changed as shown in Table 4. Furthermore, external addition was performed in the same manner as in Example 1 to obtain toners 2 to 21 and comparative toners 1 to 9. The physical properties of the toners are shown in Table 2. Furthermore, the results of evaluation by the toner evaluation method described below are shown in Table 3. From the above analysis, in toners 1 to 2 to 21 and comparative toners 1 to 9, each monomer unit forming a crystalline resin was contained in the same content ratio as in the formulation shown in Table 1.
[0111] [Table 4] In the table, the parts are parts by weight. The release agents are as follows: HNP9 is a paraffin wax manufactured by Nippon Seiro Co., Ltd., with a melting point of 75°C. WEP-5 is a monofunctional ester wax manufactured by NOF Corporation, Nissan Electol WEP-5, with a melting point of 85°C.
[0112] As is clear from Table 3, Examples 1 to 21 have superior low-temperature fixability and heat-resistant storage stability, and are also superior in color reproducibility and image gloss uniformity, as compared with Comparative Examples 1 to 9.
[0113] The present disclosure relates to the following configurations. (Configuration 1) A toner having toner particles containing a binder resin and a release agent, The binder resin includes a crystalline resin and an amorphous resin, In the differential scanning calorimetry of the toner, the toner is heated from 20° C. to 180° C. at a heating rate of 10° C. / min to obtain a differential scanning calorimetry curve A, then held at 180° C. for 10 minutes, and then cooled from 180° C. to 10° C. at a heating rate of 10° C. / min to obtain a differential scanning calorimetry curve B. , The differential scanning calorimetric curve A has an endothermic peak m(B) derived from the crystalline resin and an endothermic peak m(W) derived from the release agent, The differential scanning calorimetric curve B has an exothermic peak c(B) derived from the crystalline resin and an exothermic peak c(W) derived from the release agent, The peak temperature (°C) of the endothermic peak m(B) is designated as Tm(B), and the peak temperature (°C) of the endothermic peak m(W) is designated as Tm(W), When the peak temperature (°C) of the exothermic peak c(B) is Tc(B) and the peak temperature (°C) of the exothermic peak c(W) is Tc(W), The Tm(B), the Tc(B), the Tm(W) and the Tc(W) are 50.0≦Tm(B)≦80.0 15.0≦Tm(B)-Tc(B)≦25.0 Tc(W)≦Tm(B) 15.0≦Tm(W)-Tc(W)≦25.0 Fulfilling The storage modulus G'(TmB) of the toner at Tm(B) [°C] is 1.0×10 5 ~1.0×10 8 Pa, A toner characterized by: (Configuration 2) 2. The toner according to claim 1, wherein the release agent comprises a polyfunctional ester wax. (Configuration 3) In the differential scanning calorimetry of the toner, after obtaining the differential scanning calorimetry curve B, the toner was held at 10° C. for 10 minutes, and then heated from 10° C. to 180° C. at a temperature increase rate of 10° C. / min to obtain a differential scanning calorimetry curve C. The differential scanning calorimetric curve C has an endothermic peak (B2) derived from the crystalline resin, The toner according to configuration 1 or 2, wherein when the peak temperature (° C.) of the endothermic peak (B2) is Tm(B2), the Tm(B) and the Tm(B2) satisfy 1.0≦Tm(B)−Tm(B2)≦10.0. (Configuration 4) The toner according to any one of configurations 1 to 3, wherein the content of the crystalline resin in the binder resin is 25.0% by mass or more. (Configuration 5) The toner according to any one of configurations 1 to 4, wherein the crystalline resin comprises a crystalline vinyl resin. (Configuration 6) The toner according to configuration 5, wherein the crystalline resin contains a monomer unit represented by the following formula (1): TIFF2025065704000007.tif36153 [In formula (1), R1 represents a hydrogen atom or a methyl group, L1 represents a single bond, an ester bond, or an amide bond, and m represents an integer of 15 to 30.] (Configuration 7) the toner particles contain a straight chain fatty acid metal salt, When the number of carbon atoms of the straight-chain fatty acid in the straight-chain fatty acid metal salt is C(b), C(b) and m in the formula (1) satisfy m-10≦C(b)≦m+10; 7. The toner according to configuration 6, wherein the valence of the metal in the linear fatty acid metal salt is divalent or greater. (Configuration 8) The release agent comprises a polyfunctional ester wax, The toner according to any one of Configurations 1 to 7, wherein the polyfunctional ester wax is at least one ester compound selected from the group consisting of ester compounds of tetravalent to octavalent alcohols and aliphatic monocarboxylic acids, and ester compounds of tetravalent to octavalent carboxylic acids and aliphatic monoalcohols. (Configuration 9) The toner according to configuration 8, wherein the polyfunctional ester wax is at least one ester compound selected from the group consisting of ester compounds of hexavalent to octavalent alcohols and aliphatic monocarboxylic acids, and ester compounds of hexavalent to octavalent carboxylic acids and aliphatic monoalcohols. (Configuration 10) 10. The toner according to any one of configurations 1 to 9, wherein the crystalline resin contains a monomer unit having a lactam structure. (Configuration 11) 11. The toner according to configuration 10, wherein the lactam structure is a five-membered ring lactam structure. (Configuration 12) 12. The toner according to any one of configurations 1 to 11, wherein the amorphous resin comprises an amorphous vinyl resin.
Claims
1. A toner having toner particles containing a binder resin and a release agent, The binder resin includes a crystalline resin and an amorphous resin, In a differential scanning calorimetric measurement of the toner, the toner was heated from 20° C. to 180° C. at a heating rate of 10° C. / min to obtain a differential scanning calorimetric curve A, and then held at 180° C. for 10 minutes, and then cooled from 180° C. to 10° C. at a heating rate of 10° C. / min to obtain a differential scanning calorimetric curve B. The differential scanning calorimetric curve A has an endothermic peak m(B) derived from the crystalline resin and an endothermic peak m(W) derived from the release agent, The differential scanning calorimetric curve B has an exothermic peak c(B) derived from the crystalline resin and an exothermic peak c(W) derived from the release agent, The peak temperature (° C.) of the endothermic peak m(B) is designated as Tm(B), and the peak temperature (° C.) of the endothermic peak m(W) is designated as Tm(W), When the peak temperature (° C.) of the exothermic peak c(B) is Tc(B) and the peak temperature (° C.) of the exothermic peak c(W) is Tc(W), The Tm(B), the Tc(B), the Tm(W) and the Tc(W) are 50.0≦Tm(B)≦80.0 15.0≦Tm(B)-Tc(B)≦25.0 Tc(W)≦Tm(B) 15.0≦Tm(W)-Tc(W)≦25.0 Fulfilling The storage elastic modulus G'(TmB) of the toner at Tm(B) [°C] is 1.0 x 10 5 ~1.0 x 10 8 Pa, A toner characterized by:
2. The toner of claim 1 , wherein the release agent comprises a multifunctional ester wax.
3. In the differential scanning calorimetry of the toner, after obtaining the differential scanning calorimetry curve B, the toner was held at 10° C. for 10 minutes, and then heated from 10° C. to 180° C. at a temperature increase rate of 10° C. / min to obtain a differential scanning calorimetry curve C. The differential scanning calorimetric curve C has an endothermic peak (B2) derived from the crystalline resin, 3. The toner according to claim 1, wherein when the peak temperature (° C.) of the endothermic peak (B2) is Tm(B2), the Tm(B) and the Tm(B2) satisfy 1.0≦Tm(B)−Tm(B2)≦10.
0.
4. The toner according to claim 1 , wherein the content of the crystalline resin in the binder resin is 25.0% by mass or more.
5. The toner according to claim 1 or 2, wherein the crystalline resin comprises a crystalline vinyl resin.
6. The toner according to claim 5 , wherein the crystalline resin contains a monomer unit represented by the following formula (1): [In formula (1), R 1 represents a hydrogen atom or a methyl group; L 1 represents a single bond, an ester bond, or an amide bond, and m represents an integer of 15 to 30.
7. the toner particles contain a straight chain fatty acid metal salt, When the number of carbon atoms of the linear fatty acid in the linear fatty acid metal salt is C(b), C(b) and m in the formula (1) satisfy m-10≦C(b)≦m+10; 7. The toner according to claim 6, wherein the valence of the metal in the straight chain fatty acid metal salt is divalent or greater.
8. The release agent comprises a polyfunctional ester wax, 3. The toner according to claim 1, wherein the polyfunctional ester wax is at least one ester compound selected from the group consisting of ester compounds of tetravalent to octavalent alcohols and aliphatic monocarboxylic acids, and ester compounds of tetravalent to octavalent carboxylic acids and aliphatic monoalcohols.
9. The toner according to claim 8, wherein the polyfunctional ester wax is at least one ester compound selected from the group consisting of ester compounds of hexa-octahydric alcohols and aliphatic monocarboxylic acids, and ester compounds of hexa-octahydric carboxylic acids and aliphatic monoalcohols.
10. The toner according to claim 1 , wherein the crystalline resin contains a monomer unit having a lactam structure.
11. The toner according to claim 10, wherein the lactam structure is a five-membered ring lactam structure.
12. The toner according to claim 1 , wherein the amorphous resin comprises an amorphous vinyl resin.
Citation Information
Patent Citations
Toner binder and toner
JP2018151619A
toner
JP2020173414A